If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 5 + -5x = -3x + 2 Reorder the terms: 5 + 2x + -5x = -3x + 2 Combine like terms: 2x + -5x = -3x 5 + -3x = -3x + 2 Reorder the terms: 5 + -3x = 2 + -3x Add '3x' to each side of the equation. 5 + -3x + 3x = 2 + -3x + 3x Combine like terms: -3x + 3x = 0 5 + 0 = 2 + -3x + 3x 5 = 2 + -3x + 3x Combine like terms: -3x + 3x = 0 5 = 2 + 0 5 = 2 Solving 5 = 2 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 6b-8b=-3 | | 3(2x-8)-4=3(x-2)-7 | | 152=73.502+3.876 | | 41+x=2-2x | | 5x-92=97-2x | | x+x+1.81=68.11 | | Z+15=13 | | 5x-64=3x | | n*4-5=3 | | 3x=36-15x | | x+2(y-5)=2y+2 | | -4(3x+4)-2x+2=-2 | | 4(a+3)=18-2(3-2)a | | 3w+2=2-10 | | 7x-6=3x-54 | | 5(n+1)+2=3(n+1)+n | | 2x-20=10-3x | | 9x+4-7x=9x+4 | | 7(8x-1)=-7+6x | | 1133.9168=2*3.14*r^2+2*3.14*r*23.5 | | 9x+7y=35 | | -3(2x+9)=-4x | | 21x+6=17x-29 | | -3(5-2x)=4x+1 | | 4(x-6)=2(2x-12) | | 2x+3(7x-5)=192 | | x+23=35 | | 1b-73=-1b-3 | | 1+n=2n+9 | | 15b+2=-28 | | 5(2x+5)+3x=-74 | | 9+4(7x+8)=-7 |